PENGARUH SUBSTITUSI TEPUNG LABU KUNING (Cucurbita moschata Durch) TERHADAP KUALITAS BOLU GULUNG - Fauziah, Fauziah; Kadirman, Kadirman; Fadilah, Ratnawaty (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research aims to produce roll cake with pumpkin flour substitution and to know the chemical characteristic of flour from substitution pumpkin flour and wheat flour produce the best roll cake. And to know the organoleptik quality of roll cake product. This research was done with proksimat analysis the all treatment of substitution from pumpkin flour and wheat flour continued with organoleptik testing on roll cake. The result of research showed that the best roll cake from panelist is product substitution pumpkin flour 25% and wheat flour 75%